2022
DOI: 10.3390/w14040575
|View full text |Cite
|
Sign up to set email alerts
|

Urban Self-Supply from Groundwater—An Analysis of Management Aspects and Policy Needs

Abstract: The use of private water wells for self-supply in developing cities has ‘mushroomed’ during recent decades, such that it is now an important component of total water-supply, but one all too frequently overlooked in official figures. Selected global experience of the phenomenon (from 10 cities in 3 continents) is succinctly summarized, and then analyzed from differing perspectives, before drawing recommendations on priorities for its improved management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
(21 reference statements)
1
11
1
Order By: Relevance
“…Self‐supply exists in a range of contexts in urban and rural settings and can be found in households which are beyond the reach of utility‐ or community managed water supplies or in households that need to complement an inadequate supply (Adeniji‐Oloukoi et al., 2013; Allen et al., 2006; Grönwall, 2016; Grönwall & Danert, 2020; Komakech & de Bont, 2018; Kulabako et al., 2010; Liddle et al., 2016; Sutton, 2009). Self‐supply services are generally unregulated and unmonitored (S. Foster et al., 2022; Grönwall & Danert, 2020; Grönwall et al., 2010). In the Asia‐Pacific, it is estimated that over 700 million people depended on self‐supply across rural and urban areas in 2018 (T. Foster et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐supply exists in a range of contexts in urban and rural settings and can be found in households which are beyond the reach of utility‐ or community managed water supplies or in households that need to complement an inadequate supply (Adeniji‐Oloukoi et al., 2013; Allen et al., 2006; Grönwall, 2016; Grönwall & Danert, 2020; Komakech & de Bont, 2018; Kulabako et al., 2010; Liddle et al., 2016; Sutton, 2009). Self‐supply services are generally unregulated and unmonitored (S. Foster et al., 2022; Grönwall & Danert, 2020; Grönwall et al., 2010). In the Asia‐Pacific, it is estimated that over 700 million people depended on self‐supply across rural and urban areas in 2018 (T. Foster et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently a new focus has emerged, addressing questions on Geographic Information Systems (GIS) studies integrated into urban water supply systems, notably in historic cities. Sustainable urban groundwater systems are considered increasingly significant in global development issues such as management, protection, distribution, safety, and services (e.g., [2,3,19,27,29,39,50]). In addition, urban population growth and improved living patterns lead to increased water use and demand.…”
Section: Discussionmentioning
confidence: 99%
“…(i) The feature paper from Foster et al [39] analyses sustainable management drivers and policy demands related to urban self-supply from groundwater. In the last decades, the use of private water wells in developing cities increased enormously but in a chaotic manner.…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the use of self-supply groundwater in urban areas of developing countries is widespread and a component of the total water supply [ [5] , [6] , [7] , [8] , [9] ]. For example, it is estimated that approximately 125 million people in Sub-Saharan Africa and 340 million people in India rely on self-supply [ 10 ].…”
Section: Introductionmentioning
confidence: 99%